The hair of the common hare (Lepus europaeus Pall.) and of the common vole (Microtus arvalis Pall.) as indicator of the environmental pollution - Paukert, J; Obrusník, I (Journal of hygiene, epidemiology, microbiology, and immunology, 1986)
We made the INAA of hair of the common hare (Lepus europaeus Pall.) and of the common vole (Microtus arvalis Pall.) living in the emission zones. Both the hare and the vole are almost exclusively herbivores; they consume relatively large amounts of contaminated food and mirror reliably the contamination degree of the respective ecosystem. The use of free-living animals for the control of the environmental quality may complete effectively the information obtained by examination of habitants. Though the free-living animals lead a rather different way of existence it has been found that the analyses of their hair correlate very well with the analyses of human hair. It may be expected that the changes of concentrations of heavy metals will manifest themselves earlier in animals than in men, because the animals are strictly tied to the local food sources. The hair samples of hares contained increased concentrations of Sm, La, Au, As, Se, Cr, Sc, Fe, Ce, Th and Co. The hair of voles showed increased concentrations of Sm, La, Zn, As, Se, Cr, Sc, Fe, Sb, Ce, Cs and Co. A conspicuous trend towards the cumulation in hair was observed in the following elements: As, Se, Sc and Fe. The increase of their concentrations in the hair of animals from the emission regions amounted as such as to 10(3)%.
Keywords: vlasy, chlupy; stopové prvky; neutronová aktivační analýza; Animals; Czechoslovakia; Trace Elements; Lagomorpha; Environmental Monitoring; Neutron Activation Analysis; Hair; Arvicolinae; Československo; monitorování životního prostředí; zvířata